HUBUNGAN KARAKTERISTIK DEMOGRAFI, JUMLAH ANAK, PENGETAHUAN DAN PERSEPSI DUKUNGAN SUAMI DENGAN MINAT PENGGUNAAN IUD - Karisa Izah Wulandari (2021)
IUD is one of the most effective and efficient long-term contraceptive methods. The Interest in using IUD has been decreasing since 2018 to 2021. This study was conducted to determine whether age, education, income, occupation, number of children, knowledge of IUD and perceptions of husband's support for IUDs will affect the interest of women of childbearing age to use IUD. The study used a cross sectional design with consecutive sampling method with a total sample of 116 respondents. Data were collected using a questionnaire and analyzed using logistic regression test. The results showed that WCBA 25.9% aged >35 years, 33.6% had higher education, 44% had income > Minimum Wage, 31.9% worked, numbered children 0-2 30.2%, had high knowledge 47.4% and had good perceived husband support 32.8% was interested in using the IUD ( 50.9%). Bivariate analysis showed that there was a significant correlation between education, income, maternal employment status, number of children owned, knowledge of IUD and perceptions of husband's support regarding IUD with interest in using IUD. It can be concluded that, the most dominant variable is the perception of husband's support with (OR=12.2) followed by income (OR=7.7), education (OR=3.6), and number of children (OR=3.3). Access to information will be easier for someone with a higher socioeconomic status. WCBA's work can also affect the contraception that will be used. A good perception of husband's support will increase interest in using the IUD. The number of children owned will affect family planning, if the number of children owned is about 0-2 WCBA will be more interested in distancing their pregnancies.